Application progress of follow-up system in patients with malignant tumors (随访清单在恶性肿瘤患者中的应用现状) - LI Qianqian (李倩倩); LI li (李莉) (中西医结合护理)
Malignant tumors are currently one of the important causes of patient death worldwide. With the change in the medical care model, the rehabilitation process for tumor patients tends to be carried out outside the hospital. Therefore, constructing an effective outpatient follow-up system has become a key link in ensuring the long-term health and quality of life of patients. This article comprehensively reviewed the concept of follow-up checklists, their construction process, and their application forms and effects in clinical practice, in order to provide medical staff with a scientific and systematic follow-up reference framework. (恶性肿瘤是导致患者死亡的重要原因之一。随着医疗护理模式改变, 肿瘤患者的生存期延长, 院外康复护理需求增高。因此, 构建有效的院外随访体系成为保障患者长期健康和生活质量的关键环节。本研究就随访清单的概念、构建过程及其在临床中的应用形式和应用效果进行综述, 以期为医护人员提供一套科学、系统的随访参考框架。)